Analisis Kekritisan dan Rasio Konversi Reaktor Cepat Berpendingin Gas dengan Variasi Fraksi Bahan Bakar UN-PuN Menggunakan Skema Burn-up Modified CANDLE Arah Radial - Irka, Feriska Handayani; Su'ud, Zaki; Irwanto, Dwi; Khotimah, Siti Nurul; Sekimoto, Hiroshi (Newton-Maxwell Journal of Physics, 2023)
Analysis of the criticality and conversion ratio of a gas-cooled fast reactor (GFR) with various UN-PuN fuel fractions using modified CANDLE scheme burn-up in radial direction has been conducted. The fuel fraction varies from 40% - 60% with 5% intervals, the cladding fraction is 10% and the coolant fraction varies from 30% -50%. Data calculations were performed using SRAC 2006 programming with JENDL 4.0 library data. The reactor is divided into 10 regions with equal volume in the radial direction. Each region is filled with natural uranium fuel without enrichment with different burn-up levels. Regions are arranged in such a way that the reactor can reach critical conditions throughout the burn-up period. The results showed that variations in the 40% fuel fraction had not been able to reach critical conditions at the beginning of life, while 45%-60% fuel fraction variations had reached reactor criticality. The conversion ratio for all fuel fractions is greater than 1, which indicates that a breeding process appears in the GFR reactor core.  The conversion ratio for all variations in fuel fractions has almost the same pattern for all regions. The first region has the largest conversion ratio value because it has natural uranium as fuel input which has the highest density compared to other regions.